Closed (Verres needle) vs. open (Hasson cannula) approach to creating pneumoperitoneum in laparoscopic cholecystectomy in patients with no previous abdominal surgery: A systematic review and meta-analysis - Arun Kumar Venkatachalapathi (22155910) (2024)
Laparoscopy is considered the gold standard for assessing and exploring the abdomen and its various organs. Laparoscopy has great diagnostic and therapeutic benefits for many abdominal diseases, making it the first choice for such purposes. Laparoscopic surgery involves insufflation of gas into the peritoneal cavity, producing pneumoperitoneum to clearly visualize the abdominal contents using an illuminated telescope field. Laparoscopy has been reported to have some complications; however, these are rare and should be considered when performing the procedure. Complications such as vascular injury, omental injury, port site hernia, port site infection, port site hematoma, and gas leakage have been reported. It has been reported that the incidence of vascular injury during laparoscopy is 2 per 10,000 cases, and also per 100,000 cases, 3.3 cases of mortality-associated major complications have been reported. Two main methods of laparoscopy for pneumoperitoneum creation have been widely used for many years: the classic closed method (Verres method, where Verres needle is used) and open method (Hasson method, where Hasson's cannula is used). Other Information Published in: Current Problems in Surgery License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cpsurg.2024.101634